On Some Layer-Based Risk Measures with Applications to Exponential Dispersion Models - Olga Furman; Edward Furman (Journal of Probability and Statistics)
Layer-based counterparts of a number of well-known risk measures have been proposed and studied. Namely, some motivations and elementary properties have been discussed, and the analytic tractability has been demonstrated by developing closed-form expressions in the general framework of exponential dispersion models.